2012
DOI: 10.1103/physreva.86.043619
|View full text |Cite
|
Sign up to set email alerts
|

Two interacting fermions in a one-dimensional harmonic trap: Matching the Bethe ansatz and variational approaches

Abstract: In this work, combining the Bethe ansatz approach with the variational principle, we calculate the ground-state energy of the relative motion of a system of two fermions with spin up and spin down interacting via a delta-function potential in a one-dimensional (1D) harmonic trap. Our results show good agreement with the analytical solution of the problem, and provide a starting point for the investigation of more complex few-body systems where no exact theoretical solution is available.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…In this way, we propose a geometrical variational wave function in the sense that where the contact interaction is dominant, this wave function is the exact one for a non-diffractive regime, while in the region where the harmonic trap is dominant, the quantum system is described by a smoothly decreasing function. This idea is a sharp advance with respect to a one used for just two fermions that already provided interesting results [22] (see also [23]). For the ground state of particles in a harmonic trap, an exact analytical solution only exists for the two-body case [24] (see also [25]).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, we propose a geometrical variational wave function in the sense that where the contact interaction is dominant, this wave function is the exact one for a non-diffractive regime, while in the region where the harmonic trap is dominant, the quantum system is described by a smoothly decreasing function. This idea is a sharp advance with respect to a one used for just two fermions that already provided interesting results [22] (see also [23]). For the ground state of particles in a harmonic trap, an exact analytical solution only exists for the two-body case [24] (see also [25]).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental progress has generated great interest for few-body problems in one-dimensional geometries for both bosonic [21][22][23][24][25][26][27][28], fermionic [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], and mixed systems [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Recently, it has been shown that for strong short-range repulsive interactions a 1D two-component Fermi system in a harmonic trap exhibits strong magnetic correlations already at the three-body level [37,40].…”
Section: Introductionmentioning
confidence: 99%
“…From a theoretical standpoint, the problem of few particles interacting in a harmonic trap has been addressed through different approaches, both exact and approximative [14][15][16][17][18][19][20]. The case of strongly interacting atoms, in particular, has been shown to be analogous to an effective 1D spin chain [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%